Tariffs and formation of free trade agreements networks. (27th November 2019) - Hur, Jung; Qiu, Larry D.
Abstract: This paper examines the formation of bilateral free trade agreements (FTAs) on the basis of country heterogeneity in the tariff level. We demonstrate that a country's unilateral incentive to form an FTA depends on the relative magnitudes of the (negative) market concession effect and the (positive) market expansion effect, both of which are determined by the tariff levels of the two FTA partner countries. Global welfare is maximised when all country pairs form FTAs. Two countries in equilibrium are more likely to form an FTA when their tariff gap is smaller or when their tariff levels are neither very high nor very low. This finding is robust to several extensions of the model. Our preliminary empirical analysis provides some evidence for the finding.